Cultural intelligence and global leadership in the globalized workplace. - Chua, Hui Xin. (2009)
This study seeks to test the relationship between the four Cultural Intelligence (CQ) dimensions (cognitive, metacognitive, motivational and behavioral) with Global Leadership Effectiveness (GLE) and Global Leadership Behavioral Complexity (GLBC). We conducted two studies (n=99) across different industries, using Global Executive Leadership Inventory (GELI), Competing Values Framework (CVF) and Cultural Intelligence Scale (CQS). Results showed that the four CQ aspects are not significantly correlated with the three components of GLE. However, through a second-level analysis, Rewarding and Giving Feedback, and Team Building are significantly correlated with cognitive CQ and behavioral CQ respectively. Significant correlations are found between most of the four factors of GLBC with motivational and behavioral CQ. Motivational CQ was found to predict Relating to People and Leading Change. Adding CQ increased the explained variance in Relating to People and Leading Change. Lastly, the research and practical implications of our findings will also be discussed.